The Strategy of Lithuanian State Security in the 21st Century - Robertas Pukenis (European Scientific Journal, ESJ, 2017)
The article analyses state security as harmonious functioning of the constitutional system without interference of any outside forces, protection of territorial integrity and undisturbed functioning of a state in all public spheres. The state security in the broadest sense is strengthened by the factors of foreign and home policy. The security is based not only on strong, well trained armed forces, equipped with modern guns but also on the entire potential of a state: the approval of citizens for armament and the willingness to defend the country; economic stability, functioning of democratic principles, positive contribution of national communities into the welfare of the society, harmonious agreement of national communities, loyalty to the Constitution of the Republic of Lithuania and the competence of the Department of State Security to neutralise the forces willing to harm the consolidation of the State; they penetrate into the governmental institutions, instigate slanderous moods against the leaders or institutions of the state via mass media. The history reminds us that the West often used to betray nations; thus the question may arise whether the NATO will succeed in defending the Baltic countries according to the binding provision of Article 5 that obligates the parties for collective defence. Therefore, Lithuania urgently needs an augmented distribution of NATO toops in the Baltics. Further strategy requires insightful diplomatic steps in oreder to preserve peace and establish friendly alliances, e. g. a stronger military cooperation with Scandinavian states, brotherhood with Latvians and Estonians and approval of the dispositions of the Polish President to create a union “from the sea to the sea”. Conclusive thoughts are based on the arguments of serious political observers, sociological research, official statistics and verified data. The aim of this article is to describe the strategy of Lithuanian Republic in the field of security in the beginning of the 21st century. The object of the article is the analysis of the ways and measures for preservation of Lithuanian statehood. The author referred to the most recent media and provided political analysis of geopolitical and historical context.